Betulinic acid attenuates lung injury by modulation of inflammatory cytokine response in experimentally-induced polymicrobial sepsis in mice. Issue 1 (January 2015) - Lingaraju, Madhu Cholenahalli; Pathak, Nitya Nand; Begum, Jubeda; Balaganur, Venkanna; Bhat, Rafia Ahmad; Ramachandra, Harish Darasaguppe; Ayanur, Anjaneya; Ram, Mahendra; Singh, Vishakha; Kumar, Dhirendra; Kumar, Dinesh; Tandan, Surendra Kumar
Highlights Betulinic acid improves survival of mice in septic-lung injury model. Betulinic acid exerts anti-inflammatory effect in CLP-induced pro-inflammatory lung damage in mice. Betulinic acid can be a therapeutic modality in treatment of pro-inflammatory lung injury in septic patients.